USE OF INCRETIN DRUGS TO HELP RESTORE FERTILITY IN PATIENTS WITH PCOS - Soares, Ana Luiza Evangelista (CIPEEX, 2025)
Introduction: Polycystic ovary syndrome (PCOS) is an endocrine-metabolic disorder with manifestations in reproductive age, caused by anovulation and ovarian morphological alterations. Among the factors that contribute to infertility in this condition are lack of ovulation, in addition to metabolic factors such as obesity and insulin resistance. Therefore, analyzing medications that have a direct relationship with metabolic improvement, with a focus on weight loss, aims to correlate glycemic and body weight control with the possibility of increased female fertility. Therefore, given the complex pathophysiology arising from the association between PCOS and obesity/hypersulinemia, greater understanding of these factors and symptoms is necessary. Objective: The objective of this study is to analyze and expand popular and scientific understanding of the important relationship between the mechanisms of incretin drugs and fertility in the diagnosis of PCOS. Method: This is a literature review using the National Library of Medicine (PubMed) and the Virtual Health Library (VHL) as databases, using the following Health and Science Descriptors (DeCS): "polycystic ovary syndrome," "fertility," and "obesity." Five articles published in English between 2020 and 2025 were selected. Results: Obesity is common in women with polycystic ovary syndrome (PCOS). PCOS and obesity are associated with reduced fertility; obesity aggravates anovulation and insulin resistance, which reduces spontaneous pregnancy rates. Furthermore, to contribute to the treatment of PCOS and the restoration of fertility in women with this comorbidity, the use of incretin drugs, such as GLP1, is being studied. These drugs promote weight loss and reduce insulin resistance, which may contribute, albeit indirectly, to restoring ovulation and improving fertility. Furthermore, lifestyle changes, including improved diet and physical activity, should be combined to support medication adherence during treatment for patients with PCOS. This condition reinforces the importance of public awareness of the treatment, as it is a medication that cannot be used during pregnancy, as data on fetal safety have not yet been completed. Therefore, to maintain patient safety before and during pregnancy, guidance is needed regarding this preconception treatment. Conclusion: Given the above, a relationship between metabolic improvement and consequent weight loss with the use of incretin drugs was demonstrated to help improve fertility in women with Polycystic Ovary Syndrome.